2018
DOI: 10.32890/jict2018.17.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Label Classification for Physical Activity Recognition From Various Accelerometer Sensor Positions

Abstract: In recent years, the use of accelerometers embedded in smartphones for Human Activity Recognition (HAR) has been well considered. Nevertheless, the role of the sensor placement is yet to be explored and needs to be further investigated. In this study, we investigated the role of sensor placements for recognizing various types of physical activities using the accelerometer sensor embedded in the smartphone. In fact, most of the reported work in HAR utilized traditional multi-class classification approaches to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A vast number of datasets for HAR [39] are available for use (Table 1) such as: HAR [19,33,53,54], WISDM [53,55,56,57], UCI HAR [35,55,58], USCHAD [19], PAMAP2 [19,37,57], OPPORTUNITY [4,35,37], UniMiB-SHAR [4], MSR Action 3D [59], RGBD-HuDaAct [59], MSR Daily Activity 3D [59], MHEALTH [60], WHARF [22], KEH [61], etc. Determining which dataset to use in a HAR application and which techniques are the most appropriate for the HAR stages in a specific context is not a trivial task at all [39].…”
Section: Impact Of Human Activity Recognition (Har) Stages On Enermentioning
confidence: 99%
“…A vast number of datasets for HAR [39] are available for use (Table 1) such as: HAR [19,33,53,54], WISDM [53,55,56,57], UCI HAR [35,55,58], USCHAD [19], PAMAP2 [19,37,57], OPPORTUNITY [4,35,37], UniMiB-SHAR [4], MSR Action 3D [59], RGBD-HuDaAct [59], MSR Daily Activity 3D [59], MHEALTH [60], WHARF [22], KEH [61], etc. Determining which dataset to use in a HAR application and which techniques are the most appropriate for the HAR stages in a specific context is not a trivial task at all [39].…”
Section: Impact Of Human Activity Recognition (Har) Stages On Enermentioning
confidence: 99%
“…These activities are classified based on feature extraction schemes that are broadly categorized as time and frequency domains. In [19,20,21,22,23,24,25] researchers have implemented the time domain and frequency domain feature extraction as a combined approach. Other researchers in [26,27,28,29,30,31] have used feature extraction in the time domain only, whilst, in [32] researchers applied the frequency domain and time-frequency domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Out of these studies, Saha et al [19] found that the ensemble classifier performs best, with an overall accuracy rate of 94% using accelerometer and gyroscope sensor data. In the research carried out by Mohamed et al [20], a combination of accelerometer data from the arm, belt and pocket analysed using rotation forest with the base learner C4.5, was found to provide the best overall classification accuracy rate of 98.9% [20]. Researchers in [21,32], and [23,24,25] have analyzed the same dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The latter requires extra work but often preferred by most researchers. On the other hand, the former is much easier whereby pre-processing on data is often executed prior to complex analysis (Mohamed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%